2008
DOI: 10.1002/pc.20553
|View full text |Cite
|
Sign up to set email alerts
|

Electrical conduction in (polyvinyl alcohol/glycogen) blend films

Abstract: Cast thin films of polyvinyl alcohol/glycogen blends of different compositions have been prepared and subjected to the electrical measurements of both currenttime and current-voltage characteristics as well as d.c. conductivity as a function of temperature. The conduction mechanisms operative in the films at different temperature and voltage ranges are estimated from the behavior of log I versus V 1/2 plots. For individual polymers, the conduction mechanism appears to be essentially a Poole-Frenkel type. On bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
1
9
0
1
Order By: Relevance
“…In addition, in sample Y4 it is observed that the activation energy increases with the increase in ZnO content. From the Arrhenius behavior the electrical conduction in the PVA/ZnO polymer composite is similar to a semiconductor and this is due to a hopping mechanism between the particles, this trend is similar to the reported works for PVA-Glycogen films [33], and for PVA with Succinic acid composite films [34].…”
Section: Resultssupporting
confidence: 88%
“…In addition, in sample Y4 it is observed that the activation energy increases with the increase in ZnO content. From the Arrhenius behavior the electrical conduction in the PVA/ZnO polymer composite is similar to a semiconductor and this is due to a hopping mechanism between the particles, this trend is similar to the reported works for PVA-Glycogen films [33], and for PVA with Succinic acid composite films [34].…”
Section: Resultssupporting
confidence: 88%
“…Also, there is qualitative heterogeneity in the scales used by the authors, who create scales for the punctual assessment using variations of the visual analog scale 14,16 . Based on this, what is effective in most studies is the realization of a questionnaire with structured questions 13,17,20,27,30,33 and the consideration of the patient's report as a marker of change 15,18,19,[21][22][23][24][25][26]28,29,31,32 to guide the use of objective tests.…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen (61.90%) studies [13][14][15][16][17]19,21,[25][26][27][28][29][30][31] had a high risk of bias and 8 (38,10%) studies 17,18,20,[22][23][24]32,33 had a low risk due to comparing individuals with changes to healthy individuals in case-control designs. As for applicability, all studies were con-teria listed for this review.…”
Section: Patient Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, research has focused on the space charge dynamics of oil-impregnated insulation paper affected by voltage level, temperature, and moisture (Morshuis and Jeroense 1997;Ciobanu et al 2002;Tang et al 2010;Zhou et al 2009;Liu et al 1998). Although studies have found that many nanoparticles improve the space charge distribution in insulation materials such as polyethylene and polyimide, there are no reports on how to improve the space charge distribution in oil-impregnated insulation paper (Fleming et al 2005;Huang et al 2009;Wang et al 2009;Zha et al 2010;Thelakkadan et al 2011;Abd El-kader et al 2009;Ahmad et al 1992).…”
Section: Introductionmentioning
confidence: 99%